Assessment of service quality in supply of pharmaceutical products - Martins, A.; Conchina, L. (22nd International Symposium on Logistics, 2017)
Supply chain management and procurement policies can strongly influence the quality of service provided by companies, therefore its ability to compete in the market. Ten years after deregulation of the pharmaceutical market in Portugal, the industry faces strong challenges. Organized purchasing groups emerged to gain bargaining power towards suppliers. Nonetheless there are traditional players (pharmacies) who remain independent. The purpose of this paper is to assess and compare the perceived quality of the service provided by the traditional distributors with the one from the economic groups, and identify which factors need to be more developed by these groups to improve its service. Twenty pharmacies were interviewed (ten belonging to a specific economic group and ten independent ones). Findings show that the main criteria for supplier selection are the commercial conditions. Although the access to more favourable purchasing prices is the leading reason for pharmacies joining the economic group, lack of fulfilment of the overall commercial advantages announced by the economic groups (such as service consistency and price, when compared to the monthly fee payed to the group) lead some pharmacies to remain independent. Pharmacies manager’s management skills were identified as an influencing factor when choosing to be part of the economic group.